Wear-resistant antibacterial thermoplastic resin composite material and preparation method thereof

By using citral/PDA/boron carbide/MgO functional fillers in thermoplastic resins, the problem of insufficient wear resistance and antibacterial properties of thermoplastic resin composites is solved, and a wider application is achieved.

CN119529417AActive Publication Date: 2025-02-28HEFEI GENIUS NEW MATERIALS CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311087590.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-28
Publication Date
2025-02-28
Estimated Expiration
2043-08-28

AI Technical Summary

Technical Problem

The existing thermoplastic resin composites have insufficient wear resistance and antibacterial properties in certain application fields, which limits their application scope.

Method used

Citral/PDA/boron carbide/MgO is used as functional fillers, and a composite material with excellent wear resistance and antibacterial properties is formed by combining it with a thermoplastic resin.

Benefits of technology

It significantly improves the wear resistance and antibacterial properties of thermoplastic resin composites, expanding its application areas.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004416581830000061
    Figure BDA0004416581830000061
  • Figure BDA0004416581830000081
    Figure BDA0004416581830000081
  • Figure BDA0004416581830000101
    Figure BDA0004416581830000101
Patent Text Reader

Abstract

The invention discloses a wear-resistant and antibacterial thermoplastic resin composite material and a preparation method thereof. The wear-resistant and antibacterial thermoplastic resin composite material is prepared from the following components in parts by weight: 90-110 parts of thermoplastic resin, 10-16 parts of functional filler and 0.1-0.5 part of an antioxidant. The invention also discloses a preparation method of the thermoplastic resin composite material. The prepared thermoplastic resin composite material has good wear resistance and antibacterial performance, can be used in the field of automobile household appliance materials, and has excellent application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of polymer materials, and in particular relates to a wear-resistant and antibacterial thermoplastic resin composite material and a preparation method thereof. Background Art

[0002] Thermoplastic resin is a widely used polymer polyester resin. Thermoplastic resin has the advantages of good fatigue resistance, good heat resistance, excellent dimensional stability, etc. However, in some specific application fields, the wear resistance and antibacterial properties of thermoplastic resin are very high. For example, when thermoplastic resin is used in lunch boxes, it is not only resistant to steam, but also can be used in microwaves or refrigerators. Therefore, plastic lunch boxes are required to have antibacterial and wear-resistant properties, because during use, microorganisms in the form of bacteria, molds, etc. as pathogens can easily infect humans, animals and plants, cause diseases, and endanger human health and life. This limits the application of thermoplastic resin composites in some specific fields.

[0003] At present, in order to improve the antibacterial properties of thermoplastic resins, the main approach is to add antibacterial agents to them, which are chemical substances that keep the growth or reproduction of certain microorganisms (bacteria, fungi, yeasts, algae and viruses, etc.) below the necessary level within a certain period of time. Antibacterial agents are substances or products with antibacterial and bactericidal properties, such as silver ions. The antibacterial mechanism of silver ions and their compounds is a contact reaction antibacterial mechanism. The silver ion contact reaction causes the destruction of common components of microorganisms or functional disorders. When a trace amount of silver ions reaches the cell membrane of microorganisms, because the latter is negatively charged, the two are firmly adsorbed by Coulomb attraction. The silver ions penetrate the cell wall and enter the cell, and react with SH groups to coagulate proteins, destroy the activity of cell synthases, and the cells lose the ability to divide and proliferate and die. Silver ions can also destroy the electron transport system, respiratory system and material transport system of microorganisms.

[0004] Although nanosilver is a commonly used inorganic antibacterial agent with good biocompatibility, environmental safety and long-lasting antibacterial properties, adding it directly to the plastic matrix will easily lead to the agglomeration of the nano antibacterial agent, which will affect its original antibacterial properties to a certain extent.

[0005] As for wear resistance, currently, inorganic fillers such as glass fiber, graphite, and molybdenum disulfide are usually added to change the surface hardness of the material, or additives such as erucic acid amide are added to improve the surface lubricity of the material. However, such materials have high abrasion, short service life, and are prone to wear on the grinding parts.

[0006] In view of these shortcomings, the present invention innovatively synthesizes a wear-resistant and antibacterial thermoplastic resin composite material, which has good wear resistance and antibacterial properties. This thermoplastic resin composite material has not been reported so far, which has very important practical significance for expanding the application field of thermoplastic resin composite materials. Summary of the invention

[0007] In view of this, the present invention innovatively synthesizes a wear-resistant and antibacterial thermoplastic resin composite material, which has excellent wear resistance and antibacterial properties, and solves the technical problem of limited wear resistance and antibacterial properties of thermoplastic resins in the prior art.

[0008] The objective of the present invention is achieved through the following technical solutions:

[0009] A wear-resistant and antibacterial thermoplastic resin composite material and a preparation method thereof, comprising the following components in parts by weight:

[0010] Thermoplastic resin 90-110 parts

[0011] Functional filler 10-16 parts

[0012] Antioxidant 0.1-0.5 parts

[0013] The functional filler is citral / PDA / boron carbide / MgO.

[0014] The preparation method of citral / PDA / boron carbide / MgO comprises the following steps:

[0015] (1) adding magnesium phosphate and ammonia water into deionized water, reacting at room temperature, filtering, washing and drying to obtain solid A;

[0016] (2) calcining solid A in a muffle furnace, and grinding it through a 500-mesh sieve after cooling to obtain solid B;

[0017] (3) Place Tris-HCl buffer solution, dopamine hydrochloride, citral, boron carbide, anhydrous ethanol, deionized water, solid B, and a cross-linking agent in a reaction vessel and react in a water bath; then filter, wash, and dry to obtain citral / PDA / boron carbide / MgO.

[0018] Preferably, in step (1), the mass ratio of magnesium phosphate to aqueous ammonia is (20-30): (30-36);

[0019] The reaction time at room temperature is 4-6 hours, and the drying is carried out by placing the mixture in a vacuum drying oven at 40-60° C. for 2-4 hours.

[0020] Preferably, the calcination in step (2) is carried out at 640-720° C. for 10-12 h.

[0021] Preferably, in step (3), the mass ratio of Tris-HCl buffer solution, dopamine hydrochloride, citral, boron carbide, anhydrous ethanol, deionized water, solid B, and cross-linking agent is (40-50): (30-40): (18-24): (30-36): (50-60): (60-70): (10-16): (0.1-0.3).

[0022] Preferably, the crosslinking agent in step (3) is vinyltriethoxysilane, dicumyl peroxide or benzoyl peroxide;

[0023] The temperature of the water bath reaction is 60-80°C and the reaction time is 8-12h.

[0024] Wherein, the Tris-HCl buffer solution in step (3) is prepared by stirring a Tris solution and an HCl solution for 8-12 hours, wherein the mass ratio of the Tris solution to the HCl solution is (30-36):(36-40).

[0025] In a further embodiment, the antioxidant is one or a mixture of tris(2,4-di-tert-butyl)phenyl phosphite (referred to as Irganox 168) from BASF, N,N'-hexane-1,6-diylbis(3-(3,5-di-tert-butyl-4-hydroxyphenylpropionamide)) (Irganox 1098) and 1,3,5-trimethyl-2,4,6-(3,5-di-tert-butyl-4-hydroxybenzyl)benzene (referred to as Irganox 1330) from BASF.

[0026] The method for preparing the thermoplastic resin composite material is characterized by comprising the following steps:

[0027] (1) Weigh 90-110 parts of a thermoplastic resin, 10-16 parts of a functional filler, and 0.1-0.5 parts of an antioxidant, mix and stir to obtain a mixture;

[0028] (2) Extruding the mixed material obtained in step (1) from an extruder and granulating it to obtain a thermoplastic resin composite material.

[0029] The thermoplastic resin is one of polyethylene (PE), polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), and polyamide 6 (PA6).

[0030] Compared with the prior art, the present invention has the following beneficial effects:

[0031] (1) The functional filler in the present application is first synthesized from MgO using magnesium phosphate and polydopamine using dopamine hydrochloride as raw materials; finally, MgO and polydopamine, citral and boron carbide are physically cross-linked to form a citral / PDA / boron carbide / MgO composite functional filler.

[0032] Mg3(PO4)2+6NH3·H2O→3Mg(OH)2+2(NH4)3PO4

[0033] 3Mg(OH)2→MgO+H2O

[0034] (2) This application innovatively prepared citral / PDA / boron carbide / MgO functional filler. After boron carbide was modified by PDA, its binding ability with citral was enhanced, and citral itself can destroy the cell membrane structure of microorganisms and inhibit protein and enzyme activity, thus having a strong killing effect on bacteria. It has strong antibacterial and anti-infective properties. On the other hand, the metal ion Mg in MgO 2+ It also has a strong inhibitory effect on bacteria. This dual bactericidal effect strengthens the antibacterial effect of thermoplastic resin composites. Therefore, the addition of citral / PDA / boron carbide / MgO functional fillers can effectively improve the antibacterial properties of thermoplastic resin composites.

[0035] (3) The boron carbide in citral / PDA / boron carbide / MgO has a very high hardness. Its presence improves the wear resistance of the thermoplastic resin composite material.

[0036] (4) The macromolecular PDA generated by polymerization in this application contains a large amount of catechol and amino groups, which can easily adsorb Mg 2+ On the one hand, it can form a chelate by coordination and complexation with it; on the other hand, it can combine with the aldehyde group in the citral structure to finally form citral / PDA / boron carbide / MgO functional filler. DETAILED DESCRIPTION

[0037] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively below in conjunction with specific embodiments. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly understood.

[0038] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.

[0039] The raw materials used in the following examples are as follows:

[0040] PBT (model 2002U), Polyplastics, Japan;

[0041] PP (model Z30S), Maoming Petrochemical;

[0042] PE (model 5070), Panjin ethylene;

[0043] PA6 (model CM1017), Toray, Japan;

[0044] PET (model 008L), Aclo, Canada;

[0045] Tris solution, Hubei Kewode Chemical Co., Ltd.;

[0046] HCl solution, Beijing Haifuda Technology Co., Ltd.;

[0047] Dopamine hydrochloride, Nanjing Wanghua Chemical Technology Co., Ltd.;

[0048] Deionized water, Xiamen Aoquan Environmental Protection Technology Co., Ltd.;

[0049] Magnesium phosphate, Hubei Dibai Chemical Co., Ltd.;

[0050] Ammonia water, Jinan Mengqiao Chemical Co., Ltd.;

[0051] Boron carbide, Shandong New Kinetic Energy Chemical Co., Ltd.;

[0052] Anhydrous ethanol, Shandong Taixi Chemical Co., Ltd.;

[0053] Cross-linking agent vinyl triethoxysilane, Shandong Shouhua Chemical Co., Ltd.;

[0054] Antioxidants (types Irganox 168, Irganox 1098, Irganox 1330), BASF.

[0055] Preparation Example 1

[0056] (1) Weigh 300 g of Tris solution and 360 g of HCl solution, place them in a reaction vessel, and stir them at room temperature for 8 h to prepare a Tris-HCl buffer solution;

[0057] (2) Weigh 200 g of magnesium phosphate, 300 g of ammonia water, and 700 g of deionized water, place them in a reaction vessel, react at room temperature for 4 h, filter, wash, and place in a vacuum drying oven at 40° C. for 2 h to obtain solid A;

[0058] (3) calcining solid A at 640° C. for 10 h in a muffle furnace, cooling, and grinding through a 500-mesh sieve to obtain solid B;

[0059] (4) Weigh 400 g of Tris-HCl buffer solution, 300 g of dopamine hydrochloride, 180 g of citral, 300 g of boron carbide, 500 g of anhydrous ethanol, 600 g of deionized water, 100 g of solid B, and 1 g of cross-linking agent vinyl triethoxysilane, place in a reaction vessel, and react in a 60° C. water bath for 8 h to obtain solution A;

[0060] (5) Solution A was filtered, washed, and dried in a vacuum oven at 50° C. for 4 h to obtain a functional filler M1 of citral / PDA / boron carbide / MgO type.

[0061] Example 1

[0062] (1) Weigh 90 parts of PP, 10 parts of functional filler M1, and 0.1 parts of Irganox 1098, mix and stir evenly to obtain a mixture;

[0063] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PP composite material P1.

[0064] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 170°C, the temperature of the second temperature zone is 230°C, the temperature of the third temperature zone is 230°C, the temperature of the fourth temperature zone is 230°C, the temperature of the fifth temperature zone is 230°C, the temperature of the sixth temperature zone is 230°C, the head temperature of the twin-screw extruder is 230°C, and the screw speed is 220r / min.

[0065] Comparative Example 1

[0066] (1) Weigh 90 parts of PP, 10 parts of antibacterial agent citral, and 0.1 parts of Irganox 1098, mix and stir evenly to obtain a mixture;

[0067] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PP composite material D1.

[0068] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 170°C, the temperature of the second temperature zone is 230°C, the temperature of the third temperature zone is 230°C, the temperature of the fourth temperature zone is 230°C, the temperature of the fifth temperature zone is 230°C, the temperature of the sixth temperature zone is 230°C, the head temperature of the twin-screw extruder is 230°C, and the screw speed is 220r / min.

[0069] Comparative Example 2

[0070] (1) Weigh 90 parts of PP, 10 parts of wear-resistant agent boron carbide, and 0.1 parts of Irganox 1098, mix and stir evenly to obtain a mixture;

[0071] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PP composite material D2.

[0072] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 170°C, the temperature of the second temperature zone is 230°C, the temperature of the third temperature zone is 230°C, the temperature of the fourth temperature zone is 230°C, the temperature of the fifth temperature zone is 230°C, the temperature of the sixth temperature zone is 230°C, the head temperature of the twin-screw extruder is 230°C, and the screw speed is 220r / min.

[0073] The PP composite materials prepared in the above Example 1 and Comparative Examples 1-2 were made into test strips using an injection molding machine. The test data are as follows:

[0074]

[0075] In general, the functional filler of the citral / PDA / boron carbide / MgO composite material added in Example 1 of the present application has antibacterial and wear-resistant properties; while in Comparative Examples 1-2, although the same amount of antibacterial agent citral and wear-resistant agent boron carbide were added respectively, the antibacterial and wear-resistant properties of the composite material prepared in Example 1 of the present application are generally better than those in Comparative Examples 1-2. Therefore, the functional fillers of the citral / PDA / boron carbide / MgO type added in the present application bring unexpected technical effects to the antibacterial and wear-resistant properties of the composite material.

[0076] Preparation Example 2

[0077] (1) Weigh 360 g of Tris solution and 400 g of HCl solution, place them in a reaction vessel, and stir them at room temperature for 12 h to prepare a Tris-HCl buffer solution.

[0078] (2) Weigh 300 g of magnesium phosphate, 360 g of ammonia water, and 900 g of deionized water, place them in a reaction vessel, react at room temperature for 6 h, filter, wash, and place in a vacuum drying oven at 60° C. for 4 h to obtain solid A.

[0079] (3) Solid A was calcined at 720° C. in a muffle furnace for 12 h, cooled, and ground through a 500-mesh sieve to obtain solid B.

[0080] (4) Weigh 500 g of Tris-HCl buffer solution, 400 g of dopamine hydrochloride, 240 g of citral, 360 g of boron carbide, 600 g of anhydrous ethanol, 700 g of deionized water, 160 g of solid B, and 3 g of cross-linking agent vinyl triethoxysilane, place them in a reaction vessel, and react in a water bath at 80° C. for 12 h to obtain solution A.

[0081] (5) Solution A was filtered, washed, and dried in a vacuum oven at 70° C. for 6 h to obtain a functional filler M2 of citral / PDA / boron carbide / MgO type.

[0082] Example 2

[0083] (1) Weigh 110 parts of PBT, 16 parts of functional filler M2, 0.1 parts of antioxidant Irganox 1098, 0.2 parts of antioxidant Irganox 168, and 0.2 parts of antioxidant Irganox 1330, mix and stir evenly to obtain a mixture;

[0084] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PBT composite material P2.

[0085] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 200°C, the temperature of the second temperature zone is 230°C, the temperature of the third temperature zone is 240°C, the temperature of the fourth temperature zone is 240°C, the temperature of the fifth temperature zone is 240°C, the temperature of the sixth temperature zone is 240°C, the head temperature of the twin-screw extruder is 240°C, and the screw speed is 300r / min.

[0086] Comparative Example 3

[0087] (1) Weigh 110 parts of PBT, 16 parts of antibacterial agent citral, 0.1 parts of antioxidant Irganox 1098, 0.2 parts of antioxidant Irganox 168, and 0.2 parts of antioxidant Irganox 1330, mix and stir to obtain a mixture;

[0088] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PBT composite material D3.

[0089] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 200°C, the temperature of the second temperature zone is 230°C, the temperature of the third temperature zone is 240°C, the temperature of the fourth temperature zone is 240°C, the temperature of the fifth temperature zone is 240°C, the temperature of the sixth temperature zone is 240°C, the head temperature of the twin-screw extruder is 240°C, and the screw speed is 300r / min.

[0090] Comparative Example 4

[0091] (1) Weigh 110 parts of PBT, 16 parts of wear-resistant agent boron carbide, 0.1 parts of antioxidant Irganox 1098, 0.2 parts of antioxidant Irganox 168, and 0.2 parts of antioxidant Irganox 1330, mix and stir evenly to obtain a mixture;

[0092] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PBT composite material D4.

[0093] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 200°C, the temperature of the second temperature zone is 230°C, the temperature of the third temperature zone is 240°C, the temperature of the fourth temperature zone is 240°C, the temperature of the fifth temperature zone is 240°C, the temperature of the sixth temperature zone is 240°C, the head temperature of the twin-screw extruder is 240°C, and the screw speed is 300r / min.

[0094] The PBT composite materials prepared in the above Example 2 and Comparative Examples 3-4 were made into strips by injection molding and tested. The test data are shown in the following table:

[0095]

[0096] In general, the wear resistance and antibacterial properties of Example 2 are better than those of Comparative Examples 3-4.

[0097] Preparation Example 3

[0098] (1) Weigh 330 g of Tris solution and 380 g of HCl solution, place them in a reaction vessel, and stir and react for 10 h at room temperature to prepare a Tris-HCl buffer solution.

[0099] (2) Weigh 250 g of magnesium phosphate, 330 g of ammonia water, and 800 g of deionized water, place them in a reaction vessel, react at room temperature for 5 h, filter, wash, and place in a vacuum drying oven at 50° C. for 3 h to obtain solid A.

[0100] (3) Solid A was calcined at 680° C. for 11 h in a muffle furnace, cooled, and ground through a 500-mesh sieve to obtain solid B.

[0101] (4) Weigh 450 g of Tris-HCl buffer solution, 350 g of dopamine hydrochloride, 210 g of citral, 330 g of boron carbide, 550 g of anhydrous ethanol, 650 g of deionized water, 130 g of solid B, and 2 g of cross-linking agent vinyl triethoxysilane, place in a reaction vessel, and react in a 70° C. water bath for 10 h to obtain solution A.

[0102] (5) Solution A was filtered, washed, and dried in a vacuum oven at 60° C. for 5 h to obtain a functional filler M3 of citral / PDA / boron carbide / MgO type.

[0103] Example 3

[0104] (1) Weigh 100 parts of PE, 13 parts of functional filler M3, 0.1 parts of antioxidant Irganox 168, and 0.2 parts of antioxidant Irganox 1098, mix and stir evenly to obtain a mixture;

[0105] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PE composite material P3.

[0106] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 120°C, the temperature of the second temperature zone is 180°C, the temperature of the third temperature zone is 180°C, the temperature of the fourth temperature zone is 180°C, the temperature of the fifth temperature zone is 180°C, the temperature of the sixth temperature zone is 180°C, the head temperature of the twin-screw extruder is 180°C, and the screw speed is 300r / min.

[0107] Comparative Example 5

[0108] (1) Weigh 100 parts of PE, 13 parts of antibacterial agent citral, 0.1 parts of antioxidant Irganox 168, and 0.2 parts of antioxidant Irganox 1098, mix and stir evenly to obtain a mixture;

[0109] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PE composite material D5.

[0110] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 120°C, the temperature of the second temperature zone is 180°C, the temperature of the third temperature zone is 180°C, the temperature of the fourth temperature zone is 180°C, the temperature of the fifth temperature zone is 180°C, the temperature of the sixth temperature zone is 180°C, the head temperature of the twin-screw extruder is 180°C, and the screw speed is 300r / min.

[0111] Comparative Example 6

[0112] (1) Weigh 100 parts of PE, 13 parts of wear-resistant agent boron carbide, 0.1 parts of antioxidant Irganox 168, and 0.2 parts of antioxidant Irganox 1098, mix and stir evenly to obtain a mixture;

[0113] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PE composite material D6.

[0114] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 120°C, the temperature of the second temperature zone is 180°C, the temperature of the third temperature zone is 180°C, the temperature of the fourth temperature zone is 180°C, the temperature of the fifth temperature zone is 180°C, the temperature of the sixth temperature zone is 180°C, the head temperature of the twin-screw extruder is 180°C, and the screw speed is 300r / min.

[0115] The PE composite materials prepared in the above Example 3 and Comparative Examples 5-6 were made into test strips by injection molding machine, and the test data are as follows:

[0116]

[0117] In general, the wear resistance and antibacterial properties of Example 3 are better than those of Comparative Examples 5-6.

[0118] Preparation Example 4

[0119] (1) Weigh 355 g of Tris solution and 395 g of HCl solution, place them in a reaction vessel, and stir them at room temperature for 11 h to prepare a Tris-HCl buffer solution.

[0120] (2) Weigh 285 g of magnesium phosphate, 345 g of ammonia water, and 795 g of deionized water, place them in a reaction vessel, react at room temperature for 5 h, filter, wash, and place in a vacuum drying oven at 55° C. for 2 h to obtain solid A.

[0121] (3) Solid A was calcined at 715° C. in a muffle furnace for 11 h, cooled, and ground through a 500-mesh sieve to obtain solid B.

[0122] (4) Weigh 485 g of Tris-HCl buffer solution, 315 g of dopamine hydrochloride, 205 g of citral, 335 g of boron carbide, 515 g of anhydrous ethanol, 635 g of deionized water, 155 g of solid B, and 2.5 g of cross-linking agent vinyl triethoxysilane, place them in a reaction vessel, and react in a 75° C. water bath for 11 h to obtain solution A.

[0123] (5) Solution A was filtered, washed, and dried in a vacuum oven at 55° C. for 6 h to obtain a functional filler M4 of citral / PDA / boron carbide / MgO type.

[0124] Example 4

[0125] (1) Weigh 85 parts of PA6, 14 parts of functional filler M4, 0.1 parts of antioxidant Irganox 1098, and 0.2 parts of antioxidant Irganox 1330, mix and stir evenly to obtain a mixture;

[0126] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PA6 composite material P4.

[0127] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 210°C, the temperature of the second temperature zone is 260°C, the temperature of the third temperature zone is 260°C, the temperature of the fourth temperature zone is 260°C, the temperature of the fifth temperature zone is 260°C, the temperature of the sixth temperature zone is 260°C, the head temperature of the twin-screw extruder is 260°C, and the screw speed is 320r / min.

[0128] Comparative Example 7

[0129] (1) Weigh 85 parts of PA6, 14 parts of antibacterial agent citral, 0.1 parts of antioxidant Irganox 1098, and 0.2 parts of antioxidant Irganox 1330, mix and stir to obtain a mixture;

[0130] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PA6 composite material D7.

[0131] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 210°C, the temperature of the second temperature zone is 260°C, the temperature of the third temperature zone is 260°C, the temperature of the fourth temperature zone is 260°C, the temperature of the fifth temperature zone is 260°C, the temperature of the sixth temperature zone is 260°C, the head temperature of the twin-screw extruder is 260°C, and the screw speed is 320r / min.

[0132] Comparative Example 8

[0133] (1) Weigh 85 parts of PA6, 14 parts of wear-resistant agent boron carbide, 0.1 parts of antioxidant Irganox 1098, and 0.2 parts of antioxidant Irganox 1330, mix and stir evenly to obtain a mixture;

[0134] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PA6 composite material D7.

[0135] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 210°C, the temperature of the second temperature zone is 260°C, the temperature of the third temperature zone is 260°C, the temperature of the fourth temperature zone is 260°C, the temperature of the fifth temperature zone is 260°C, the temperature of the sixth temperature zone is 260°C, the head temperature of the twin-screw extruder is 260°C, and the screw speed is 320r / min.

[0136] The PA6 composite materials prepared in the above Example 4 and Comparative Examples 7-8 were made into test strips by injection molding machine, and the test data are as follows:

[0137]

[0138] In general, the wear resistance and antibacterial properties of Example 4 are better than those of Comparative Examples 7-8.

[0139] Preparation Example 5

[0140] (1) Weigh 345 g of Tris solution and 385 g of HCl solution, place them in a reaction vessel, and stir at room temperature for 9 h to prepare a Tris-HCl buffer solution.

[0141] (2) Weigh 215 g of magnesium phosphate, 335 g of ammonia water, and 885 g of deionized water, place them in a reaction vessel, react at room temperature for 5 h, filter, wash, and place in a vacuum drying oven at 55° C. for 4 h to obtain solid A.

[0142] (3) Solid A was calcined at 705°C in a muffle furnace for 11 h, cooled, and ground through a 500-mesh sieve to obtain solid B.

[0143] (4) Weigh 425 g of Tris-HCl buffer solution, 375 g of dopamine hydrochloride, 225 g of citral, 345 g of boron carbide, 525 g of anhydrous ethanol, 655 g of deionized water, 145 g of solid B, and 2.8 g of cross-linking agent vinyl triethoxysilane, place in a reaction vessel, and react in a 75° C. water bath for 9 h to obtain solution A.

[0144] (5) Solution A was filtered, washed, and dried in a vacuum oven at 65° C. for 5 h to obtain a functional filler M5 of citral / PDA / boron carbide / MgO type.

[0145] Example 5

[0146] (1) Weigh 95 parts of PET, 13.5 parts of functional filler M5, 0.1 parts of antioxidant Irganox 1098, and 0.1 parts of antioxidant Irganox 168, mix and stir to obtain a mixture;

[0147] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PET composite material P5.

[0148] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 240°C, the temperature of the second temperature zone is 280°C, the temperature of the third temperature zone is 280°C, the temperature of the fourth temperature zone is 280°C, the temperature of the fifth temperature zone is 280°C, the temperature of the sixth temperature zone is 280°C, the head temperature of the twin-screw extruder is 280°C, and the screw speed is 280r / min.

[0149] Comparative Example 9

[0150] (1) Weigh 95 parts of PET, 13.5 parts of antibacterial agent citral, 0.1 parts of antioxidant Irganox 1098, and 0.1 parts of antioxidant Irganox 168, mix and stir to obtain a mixture;

[0151] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PET composite material D9.

[0152] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 240°C, the temperature of the second temperature zone is 280°C, the temperature of the third temperature zone is 280°C, the temperature of the fourth temperature zone is 280°C, the temperature of the fifth temperature zone is 280°C, the temperature of the sixth temperature zone is 280°C, the head temperature of the twin-screw extruder is 280°C, and the screw speed is 280r / min.

[0153] Comparative Example 10

[0154] (1) Weigh 95 parts of PET, 13.5 parts of anti-wear agent boron carbide, 0.1 parts of antioxidant Irganox 1098, and 0.1 parts of antioxidant Irganox 168, mix and stir to obtain a mixture;

[0155] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PET composite material D10.

[0156] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 240°C, the temperature of the second temperature zone is 280°C, the temperature of the third temperature zone is 280°C, the temperature of the fourth temperature zone is 280°C, the temperature of the fifth temperature zone is 280°C, the temperature of the sixth temperature zone is 280°C, the head temperature of the twin-screw extruder is 280°C, and the screw speed is 280r / min.

[0157] The PET composite materials prepared in the above Example 5 and Comparative Examples 9-10 were made into strips by injection molding and tested. The test data are shown in the following table:

[0158]

[0159] In general, the wear resistance and antibacterial properties of Example 5 are better than those of Comparative Examples 9-10.

[0160] It can be seen from the above embodiments and comparative examples that the thermoplastic resin composite material prepared by the method provided by the present invention has excellent wear resistance and antibacterial properties, and can expand the application field of the thermoplastic resin composite material.

[0161] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0162] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A wear-resistant and antibacterial thermoplastic resin composite material, characterized in that: It is composed of the following components by weight: Thermoplastic resin 90-110 parts Functional filler 10-16 parts Antioxidant 0.1-0.5 parts The functional filler is citral / PDA / boron carbide / MgO.

2. The thermoplastic resin composite material according to claim 1, characterized in that: The preparation method of citral / PDA / boron carbide / MgO comprises the following steps: (1) adding magnesium phosphate and ammonia water into deionized water, reacting at room temperature, filtering, washing and drying to obtain solid A; (2) calcining solid A in a muffle furnace, and grinding it through a 500-mesh sieve after cooling to obtain solid B; (3) Place Tris-HCl buffer solution, dopamine hydrochloride, citral, boron carbide, anhydrous ethanol, deionized water, solid B, and a cross-linking agent in a reaction vessel and react in a water bath; then filter, wash, and dry to obtain citral / PDA / boron carbide / MgO.

3. The thermoplastic resin composite material according to claim 2, characterized in that: In step (1), the mass ratio of magnesium phosphate to aqueous ammonia is (20-30): (30-36); The reaction time at room temperature is 4-6 hours, and the drying is carried out by placing the mixture in a vacuum drying oven at 40-60° C. for 2-4 hours.

4. The thermoplastic resin composite material according to claim 2, characterized in that: The calcination in step (2) is carried out at 640-720° C. for 10-12 hours.

5. The thermoplastic resin composite material according to claim 2, characterized in that: In step (3), the mass ratio of Tris-HCl buffer solution, dopamine hydrochloride, citral, boron carbide, anhydrous ethanol, deionized water, solid B, and cross-linking agent is (40-50): (30-40): (18-24): (30-36): (50-60): (60-70): (10-16): (0.1-0.3).

6. The thermoplastic resin composite material according to claim 2, characterized in that: The crosslinking agent in step (3) is vinyltriethoxysilane, dicumyl peroxide or benzoyl peroxide; The temperature of the water bath reaction is 60-80°C and the reaction time is 8-12h.

7. The thermoplastic resin composite material according to claim 2, characterized in that: In step (3), the Tris-HCl buffer solution is prepared by stirring a Tris solution and a HCl solution for 8-12 hours, wherein the mass ratio of the Tris solution to the HCl solution is (30-36):(36-40).

8. The thermoplastic resin composite material according to claim 1, characterized in that: The antioxidant is one or a mixture of tris(2,4-di-tert-butyl)phenyl phosphite, N,N'-hexane-1,6-diylbis(3-(3,5-di-tert-butyl-4-hydroxyphenylpropionamide)) and 1,3,5-trimethyl-2,4,6-(3,5-di-tert-butyl-4-hydroxybenzyl)benzene.

9. The thermoplastic resin composite material according to claim 1, characterized in that: The thermoplastic resin is one of polyethylene, polypropylene, polyethylene terephthalate, polybutylene terephthalate and polyamide 6.

10. The method for preparing a thermoplastic resin composite material according to any one of claims 1 to 9, characterized in that: The following steps are involved: (1) Weigh 90-110 parts of thermoplastic resin, 10-16 parts of functional filler, and 0.1-0.5 parts of antioxidant, mix and stir evenly to obtain a mixture; (2) Extruding the mixed material obtained in step (1) from an extruder and granulating it to obtain a thermoplastic resin composite material.

Citation Information

Patent Citations

  • Antibacterial and abrasion-resistant ABS (acrylonitrile-butadiene-styrene) composite material and method for preparing same

    CN108752845A

  • Self-antibacterial polyetheramine derivative modified styrene-acrylic emulsion paint and preparation method thereof

    CN110845930A

  • Heat-conducting antibacterial thermoplastic resin composite material and preparation method thereof

    CN116285112A